Konstruksi Ideologi Dalam Wacana Video “Darurat Militer”; Analisis Wacana Kritis Pendekatan Norman Fairclough - Ester Reviani Manullang; Hera Chairunisa; Syairal Fahmy Dalimunthe (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study analyzes the discourse surrounding the declaration of a military emergency in Indonesia, focusing on digital media content, particularly videos produced by content creator Ferry Irwandi. This research employs Norman Fairclough's Critical Discourse Analysis (CDA) framework to uncover the ideological constructions and power relations embedded in the discourse. Three videos analyzed include "Dalang Demo dan Mencegah Darurat Militer," "Indonesia (Tidak) Gelap?" and "Berani Masuk Penjara, Ferry Irwandi Bawa Video Bongkar Dalang Kericuhan Demo." The study highlights how media frames the crisis, power dynamics, and societal roles during demonstrations. The findings indicate that media not only conveys information but also shapes public opinion, influences existing political ideologies, and challenges dominant narratives constructed by the government and mainstream media.